Islamic Bank As A Role Model of Implementation Tawhidi String Relations in Production Concept - Siti Nurdiana; Tatik Mariyanti (Indonesian Journal of Business, Accounting and Management (IJBAM), 2021)
This study describes how the role of the Islamic bank as an Islamic enterprise in well-being functions. The Well-being Function is derived from Tawhidi String Relations (TSR) Methodology by (Choudury & Hasan [3]) for evaluating how well-being is reached because of interaction-integration-evolution of inputs and outputs which have been induced by theta as a symbol of knowledge derived from Al-Quran and Hadits [1] through shuratic process. This study added Umma (zakat) and Government (tax) as indirect (intervening) variables to the Well-being equation to interact with input, output, and Islamic Bank as an Islamic Enterprise. Besides for simplifying analysis, this study also merged variable employment (L), and Human Capital (H) become human capital (H) only. The result is that the practice of Islamic Banks fit in Islamic Production concept, which are mobilizing funds by the halal way and financing only for halal sectors through Sharia Ways by avoiding maisyir, gharar, and riba. Islamic Bank brings maslaha, gives goodness and benefit to others and society (stakeholders), and avoids humanity from badness or destruction. Inputs and output in Islamic Bank justly and equitably interconnect in circular causation and grow together as pairs for reaching well-being. Bank’s income justly and equitably distributed to human capital, shareholders, and shahibul maal as the owner of capital, Ummah in the form of Zakat and Tax for Government. Fine categorized as non-halal income is also distributed as a charity for building Masjid or other good deeds.